Why patents need reform, and some suggestions for it - KINGSTON, WILLIAM (Edward Elgar, 2009)
The patent system no longer fulfills its original purpose, but it could be repaired and this chapter shows some ways of doing this.
PUBLISHED
Keywords: intellectual property reform